2020
DOI: 10.1038/s41598-020-77258-w
|View full text |Cite
|
Sign up to set email alerts
|

Validation of deep learning natural language processing algorithm for keyword extraction from pathology reports in electronic health records

Abstract: Pathology reports contain the essential data for both clinical and research purposes. However, the extraction of meaningful, qualitative data from the original document is difficult due to the narrative and complex nature of such reports. Keyword extraction for pathology reports is necessary to summarize the informative text and reduce intensive time consumption. In this study, we employed a deep learning model for the natural language process to extract keywords from pathology reports and presented the superv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 26 publications
0
33
0
Order By: Relevance
“…Modeling of the epilepsy dataset with the LSTM, BiLSTM, and CNN models, which are popular deep learning models, are presented comparatively. When this study is compared to other works [6][7][8][9][10][11][12][13][14][15][16][17][18][19], no study like this study was found for the actual MRI data set of patients with the epilepsy. Among our proposed methods, due to the BiLSTM network's ability to operate both backward and forward information, it has been proven to give the best classification result.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Modeling of the epilepsy dataset with the LSTM, BiLSTM, and CNN models, which are popular deep learning models, are presented comparatively. When this study is compared to other works [6][7][8][9][10][11][12][13][14][15][16][17][18][19], no study like this study was found for the actual MRI data set of patients with the epilepsy. Among our proposed methods, due to the BiLSTM network's ability to operate both backward and forward information, it has been proven to give the best classification result.…”
Section: Discussionmentioning
confidence: 92%
“…The clinical reports for the breast pathology were identified by the rule based and boosting methods in the [15] by the 97% classification accuracy rate. The pathology reports were analyzed for the keyword extraction by the fine-tuning and deep learning approaches in the [16]. The bidirectional encoder representations from transformers model was successful model for the precision and recall values.…”
Section: Introductionmentioning
confidence: 99%
“…Other excellent applications of BERT-based text models include the prediction of relative value units (RVU’s) via report complexity for pathologist compensation calculations (which is related to primary code assignment) and the detection of cases that may have been mis-billed (e.g., a code of lower complexity was assigned), which can potentially save the hospital resources. [ 61 ] We are currently developing a web application that will both interface with the Pathology Information System and can be used to estimate the fiscal impact of underbilling by auditing reports with false positive findings. Tools such as Inspirata can also provide additional structuring for our pathology reports outside of existing schemas.…”
Section: Discussionmentioning
confidence: 99%
“…In formula (10), p 1 and p 2 represent the conditional probability of intention label and slot label; M v 2 represents the probability vector of softmax transport slot label corresponding to each word; v represents the number of corresponding slot labels; M 1 represents the intention probability vector output by softmax. e probability of the corresponding category in each dimension and the maximum probability are taken as the intention category predicted by the sample [33]. Intent recognition and slot filling share the same encoder.…”
Section: Establishing Spoken Language Understanding Modelmentioning
confidence: 99%